PENGGUNAAN MODEL STRUKTURAL ANALITIK SINTETIK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS II SEKOLAH DASAR - Sinta Santika; Asep Samsudin (STKIP Subang, 2022)
Students' comprehension in reading is said to be still low, as well as what happened to the fifth grade elementary school students. This low understanding is due to the lack of interest in reading and the assumption that reading is boring and meaningless. Therefore, the teacher should choose the right technique to overcome this problem. By using the SAS model with discussion techniques it is hoped that it can overcome the problems encountered. The subject of this research is reading comprehension ability. Data collection using pre test and post test techniques. From the results of the study, it showed that there was an average increase in students' understanding of reading ability from 68.4 during cycle 2 to 78.